The Movement of Women's Thoughts from Pesantren: Study of the Jam'iyyah Pengasuh Pesantren Putri and Muballighah (JP3M) - Aziz, Abdul; Mamluatun Nurrohmah (UIN Raden Mas Said Surakarta, 2022)
Bu Nyai is a figure who is not much different from kiai, because they have a big role in shaping the knowledge, attitudes and activities of students in the pesantren. In this case, the pesantren which is the center of the activity has a vital position, especially with regard to gender, because here it is the basis which is considered the center of patriarchal teachings. But as time went on, this assumption was dismissed and crushed by the JP3M Movement. This movement represents the courage of Bu Nyai in their efforts to review and revise their cynical assumptions. This movement contributes to highlighting the role of women in the dimensions of community life, especially for science, gender and brotherhood or ukhuwah. This is a great strength, because with their charisma they can influence students, especially female students, to be proactive in improving the image of women as agents of change. This important effort also became the forerunner of pesantren circles, especially for women to create a meeting movement to give birth to women with dignity in accordance with ethics, religious morals, and social life.